Mesenchymal Stem Cell-Derived Extracellular Vesicles in Liver Immunity and Therapy - Wu, Ruiqi; Fan, Xiaoli; Wang, Yi; Shen, Mengyi; Zheng, Yanyi; Zhao, Shenglan; Yang, Li (Frontiers in Immunology, 2022)
Mesenchymal stem cells (MSCs), as the most common cell source for stem cell therapy, play an important role in the modulation of innate and adaptive immune responses and have been widely used in clinical trials to treat autoimmune and inflammatory diseases. Recent experimental and clinical studies have shown that MSC-derived extracellular vesicles (MSC-EVs) can inhibit the activation and proliferation of a variety of proinflammatory cells, such as Th1, Th17 and M1 macrophages, reducing the secretion of proinflammatory cytokines, while promoting the proliferation of anti-inflammatory cells, such as M2 macrophages and Tregs, and increasing the secretion of anti-inflammatory cytokines, thus playing a role in immune regulation and exhibiting immunomodulatory functions. Besides MSC-EVs are more convenient and less immunogenic than MSCs. There is growing interest in the role of MSC-EVs in liver diseases owing to the intrinsic liver tropism of MSC-EVs. In this review, we focus on the immunomodulatory effects of MSC-EVs and summarize the pivotal roles of MSC-EVs as a cell-free therapy in liver diseases, including NAFLD, AIH, acute liver failure, liver fibrosis and hepatic ischemia–reperfusion injury. Moreover, we provide a concise overview of the potential use and limits of MSC-EVs in clinical application.